Transfer Teknologi Optimalisasi Penggunaan Set Top Box (STB) Televisi Digital Bagi Masyarakat Kelurahan Gebangsari Kecamatan Genuk Kota Semarang - Budisusila, Eka Nuryanto; Ismail, Munaf; Hapsari, Jenny Putri (Journal of Appropriate Technology for Community Services, 2024)
The Indonesian government's policy of deactivating analog television broadcasts and switching to digital television has an impact on people who are still used to enjoying analog television broadcasts. Moreover, many television devices owned by the public are still analog system televisions. Thus, people need devices that can convert analog signals into digital form and can be displayed on analog television. This device is better known as a Set Top Box (STB). Unfortunately, people only use STB to watch digital TV shows, while STB has many features that can be used to obtain information, communication tools and entertainment media. For this reason, it is necessary to transfer knowledge and technology to the community so that it can optimize the functions and features of the STB, then these activities are packaged in the form of Community Service. The results of the activity showed that the public was very enthusiastic in following and concerning to the presentation of information on STB features, proven by the large number of people who attended, reaching 93% of the invitations given, and the many questions asked during the discussion session.